CDR 2019
DOI: 10.20517/cdr.2019.68
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in neuroblastoma tumorigenesis, therapy resistance, and disease evolution

Abstract: Neuroblastoma (NB) deriving from neural crest cells is the most common extra-cranial solid cancer at infancy. NB originates within the peripheral sympathetic ganglia in adrenal medulla and along the midline of the body. Clinically, NB exhibits significant heterogeneity stretching from spontaneous regression to rapid progression to therapy resistance. MicroRNAs (miRNAs, miRs) are small (19-22 nt in length) non-coding RNAs that regulate human gene expression at the post-transcriptional level and are known to reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 168 publications
(179 reference statements)
1
28
0
Order By: Relevance
“…Dysregulation of miRNAs has been reported in numerous cancers where individual miRNAs behave in an oncogenic or tumor suppressor manner [11][12][13][14]. To date, several profiling studies have reported that miRNAs are associated with clinical outcome in NB [15] and specific miRNAs have been identified to regulate key processes such as apoptosis, differentiation, cell proliferation and cell invasiveness in NB [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of miRNAs has been reported in numerous cancers where individual miRNAs behave in an oncogenic or tumor suppressor manner [11][12][13][14]. To date, several profiling studies have reported that miRNAs are associated with clinical outcome in NB [15] and specific miRNAs have been identified to regulate key processes such as apoptosis, differentiation, cell proliferation and cell invasiveness in NB [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, almost 30% of neuroblastoma patients show the MYCN amplification [ 48 ]. The correlation between oncogene amplification and increased tumor aggressiveness has been extensively studied; nevertheless, since MYC is involved in several cellular pathways, the role of this oncogene in tumor progression has not yet been fully elucidated [ 49 , 50 ]. Accordingly, in this study we found that the autocrine response of MYCN -amplified SK-N-BE cells to EVs was similar or even greater than the one observed in SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Aravindan et al have published a comprehensive review on the key role of microRNAs-loaded exosomes in neuroblastoma multi-drug resistance [ 50 ]; other authors have investigated pathways in neuroblastoma cells that are important in determining radio-resistance [ 51 ]. Abramowicz et al reviewed the role of EVs released by cells subjected to environmental physicochemical stress in regulating proliferation, cell survival, migration, and angiogenesis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR126-3P suppresses SOX2 expressions in GBM patients sensitizing tumor cells to temozolomide (TMZ) treatment [20]. In NB, induced and upregulated expression of miR-340 inhibits SOX2 expressions implicating its role in countering therapy resistance [21]. All these facts indicate a critical role of SOX2 in initiation, progression, and sustenance of cancer, signifying the importance of exosomal SOX2 DNA analysis.…”
Section: Competing Interestsmentioning
confidence: 99%